2014
DOI: 10.3390/en7117348
|View full text |Cite
|
Sign up to set email alerts
|

Design Optimization of Heat Wheels for Energy Recovery in HVAC Systems

Abstract: Air to air heat exchangers play a crucial role in mechanical ventilation equipment, due to the potential primary energy savings both in case of refurbishment of existing buildings or in case of new ones. In particular, interest in heat wheels is increasing due to their low pressure drop and high effectiveness. In this paper a detailed optimization of design parameters of heat wheels is performed in order to maximize sensible effectiveness and to minimize pressure drop. The analysis is carried out through a one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…The characteristics of the rotary heat exchanger are introduced by applying the function of porous material. In this case, the porosity of the material σ, the ratio between the surface area and volume A/V and the heat transfer rate h T are introduced [13]. First, the problem is approached in a stationary mode until the air velocity and temperature stabilizes while the rotor is not running.…”
Section: Fig 3 the Finite Volume Network Of The Rotary Heat Exchanger Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…The characteristics of the rotary heat exchanger are introduced by applying the function of porous material. In this case, the porosity of the material σ, the ratio between the surface area and volume A/V and the heat transfer rate h T are introduced [13]. First, the problem is approached in a stationary mode until the air velocity and temperature stabilizes while the rotor is not running.…”
Section: Fig 3 the Finite Volume Network Of The Rotary Heat Exchanger Modelmentioning
confidence: 99%
“…The literature review has shown that once the rotational speed of the rotary heat exchanger reaches a certain value, there is virtually no effect on the temperature efficiency [2], [5] and [13]. The results of a large number of studies show that this value does not exceed 12 revolutions per minute.…”
Section: Research Scopementioning
confidence: 99%
See 2 more Smart Citations
“…The cooling tower display is approved utilizing test information in a pilot plant. In [27], a point by point enhancement of plan parameters of warmth wheels is performed with a specific end goal to amplify sensible viability and to limit pressure drop. The investigation is brought out through a one-dimensional lumped parameters heat wheel model, which settles heat and mass exchange conditions, and through suitable relationships to appraise pressure drop.…”
Section: Introductionmentioning
confidence: 99%